CONSEQUENCE MODELLING OF PRESSURIZED C02 RELEASE IN PURE AND RICH MIXTURE WITH OBSTACLES - PHAM HOANG, HUY PHUOC LOI (2014)
Carbon capture and storage (CCS) is an alternative for decreasing greenhouse gas (GHG) emissions by removing carbon dioxide (CO2) from power plants. Accidental discharges from CCS plant will result in a release of dense CO2 gas cloud to the ambience at high concentrations which becomes a dominated threat to human health. Based on the current research, there is a knowledge gap in assessing the release of CO2 via pipeline leakage. Thus, it is necessary to develop an accurate consequence model for CO2 release in order to demonstrate a safe layout and other safeguards. In this study, pure CO2 discharge and dispersion were detailed out using a threedimension model with presence ofobstacles in a computational fluid dynamics (CFD) software. Realizable k-e turbulence model was chosen for simulating the dispersion of pure C02-air. From there, trial 3-7 of Kit Fox gas experiments of pure CO2 instantaneous release was further developed to evaluate discharge scenario. Results obtained from the model were compared with experimental data from literatures and validation was achieved. Then this model was extended to simulate a case study of CO2 releases with other toxic impurities which are hydrogen sulfide (H2S). Extension indicated the validated model can approximately predict time-varying concentrations of CO2 and H2S at any point in CO2 cloud when mixed with H2S. Finally, overall fatality rates due to both CO2 and H2S at some selected points can be estimated using a dose - response model. Conclusive evidence shows that the developed CFD model is a reliable method for assessing the consequences ofaccidental releases of CO2.